2021
DOI: 10.21865/ridep60.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Inventario de Ideación Suicida Positiva y Negativa (PANSI): Propiedades Psicométricas en Universitarios Peruanos

Abstract: Es necesario contar con instrumentos que evalúen la ideación suicida, dado que es uno de los primeros factores que conllevan al suicidio. La presente investigación realizó un proceso de adaptación del Inventario de Ideación Suicida Positiva y Negativa (PANSI) para que pueda ser empleado en universitarios peruanos. Se estudiaron dos muestras, una antes y otra durante la pandemia por COVID-19. A nivel metodológico, se siguió un procedimiento racional con jueces expertos y con sujetos de la población para consegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…This adaptation of the scale showed overall good internal consistency. Despite the fact that item 4 raised the subscale's alpha, this increase was minimal, and the subscales generally showed similar or better internal consistency than other versions (e.g., [15,17]).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This adaptation of the scale showed overall good internal consistency. Despite the fact that item 4 raised the subscale's alpha, this increase was minimal, and the subscales generally showed similar or better internal consistency than other versions (e.g., [15,17]).…”
Section: Discussionmentioning
confidence: 81%
“…The original version was validated with university students [6] and has since been adapted for use among inpatient samples [7], high school students [8], and young adults [5]. It has also been validated adapted to various languages and countries, such as Colombia and Mexico [9,10], China [11,12], Pakistan [13], Malaysia [14], Nigeria [15], Spain [16], and Peru [17]. In all versions of this scale, a twofactor structure confirming the stated purpose emerged, both factors showed good internal consistency, and all 14 items of the original version were retained; more detailed information can be found in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Univariate ANOVA revealed that Subjects with a higher score of academic procrastination and BDI-II reported higher scores for suicidal ideation than those with a lower score (P < 0.01) ( Table 4 ). Based on previous studies, the score of 17 in the academic procrastination questionnaire is considered as the cut-off point ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Positive and Negative Suicidal Ideation Inventory (PANSI), created by Osman et al . and adapted for use in Peru by Rodas-Vera et al ( 23 ), was used to evaluate the variable of suicidal ideation. The scale has two dimensions, consisting of 14 items, six for positive suicidal ideation (protective factors) and eight for negative suicidal ideation (risk factors), and is applied to people between the ages of 17 and 32.…”
Section: Methodsmentioning
confidence: 99%
“…Inventario de Ideación Suicida Positiva y Negativa (PANSI; Osman et al, 1998). Se utilizó la adaptación peruana (RodasVera et al, 2021), cuyas propiedades psicométricas antes de la pandemia (SRMR = .038, RM-SEA = .061) y durante la pandemia por COVID19 (SRMR = .045, RMSEA = .078) resultaron excelentes para población universitaria. Presenta 16 ítems distribuidos en dos dimensiones: ideación suicida negativa e ideación suicida positiva.…”
Section: Instrumentosunclassified